Knowledge translation in times of the COVID-19 pandemic in quilombola community - Nunes Moraes-Partelli, Adriana; Amabiles Pazini, José Marcos; Pestana Santos, Aline; Lorencini Santos, Isabela; Pereira Coelho, Marta (Guará Journal, 2023)
OBJECTIVE:  To  illustrate  the  translation  of  knowledge  in  the  format  of  educational  health  material  carried  out  in  times  of  a  pandemic  for quilombola community.  METHODOLOGY:  Qualita-tive  and bibliographic  study,  developed  in  the  following stages:  1) Survey of scientific content on COVID-19 through bibliographic research;  2)  Production  of  a booklet  with  information  on  conta-gion, dissemination and how to prevent COVID-19 in the quilom-bola community, considering the rgoup with ancestors from the African continent.; and 3) Delivery of the booklet to the Municipal Health Department for distribution to the Health Units that have quilombola communities in their territory. RESULTS: The literatu-re review contributed scientifically to the survey of themes for the composition  of  the  booklet.  Afterwards,  a  storyboard  was  crea-ted where the illustrations, the textual content and the language used were defined. A company was hired that illustrated and dia-grammed the final product: “Quilombola community in focus: on preventing the contagion and spread of the Coronavirus”. The de-livery of 680 printed copies of the booklet was made to the Muni-cipal Health Department of São Mateus. CONCLUSION: This study was developed by applying the university pillar (teaching-resear-ch-extension), which directly impacted the training of undergra-duate students and culminated in the production of educational technology containing content with an urgent and current social problem, contributing to the inclusion of social groups in a situa-tion of vulnerability.
Keywords: Coronavirus infections; Health education; Communicable disease control; Group with ancestors from the african continent